Сенсори газів на наноструктурах: сучасний стан та перспективи досліджень - Бурий, О. А.; Убізський, С. Б.; Buryy, O.; Ubizskii, S. B. (Видавництво Львівської політехніки, 2017)
Проаналізовано основні досягнення у галузі розроблення газових сенсорів резис- тивного типу, зокрема, створення нових наноархітектур, які дають змогу істотно покра- щити робочі характеристики сенсорів. Показано, що використання у таких структурах середовищ на основі нанокристалів перовськитів дасть можливість в перспективі забез- печити переваги над сенсорами на традиційних напівпровідникових оксидах металів.

The analysis of the progress in the field of the resistive gas sensors elaboration is carried out. Particularly, the novel nanoarchitectures that allow to essentially increase the sensors operating characteristics are described. As it is shown, high sensitivity, fast response, short recovery time, a considerable number of detected gases, low detection limit (about 1 ppm), reliability, compactness, relative simplicity of fabrication and low cost can be achieved due to nanostructured resistive gas sensors using. The improvement of characteristics of such sensors, particularly, their sensitivity, is caused by significant decrease of inter-particle barriers in nanopowders or other nanostructures. The elaboration of nanostructured gas sensors based on perovskite nanocrystalline media will ensures the advantages in comparison with traditional semiconductor oxide gas sensors. Particularly, their stability and selectivity are eventually higher and the operating temperature is lower than the ones of traditional SnO2- or ZnO-based gas sensors. The other advantages of perovskites are the possibility of isomorphic substitution of atoms that allows to change their compostion in the wide range, relative simplicity and the modest cost of nanopowder sintering by sol-gel technique. At the current time, however, the selectivity of perovskite nanostructured resistive gas sensors is not high enough that stipulates the additional investigations for the improvement of this parameter. The possible directions of these investigations are defining of the optimal composition of the material as well the determination of optimal grain size and porosity. One more important task is the construction of the realistic mathematical models of nanostructured gas sensors that allows to foresee the possible ways of such optimization.
Nanostructured gas sensors: the state of the art and perspectives for research
Keywords: сенсори газів; наноструктуровані матеріали; перовськіти; gas sensors; nanostructures materials; perovskites; 537.312